Cumberland blood : Champ Ferguson's Civil War - Mays, Thomas D., 1960- (Southern Illinois University Press, 2008)
By the end of the Civil War, Champ Ferguson had become a notorious criminal whose likeness covered the front pages of Harper's Weekly, Leslie's Illustrated, and other newspapers across the country. His crime? Using the war as an excuse to steal, plunder, and murder Union civilians and soldiers. Cumberland Blood: Champ Ferguson's Civil War offers insights into Ferguson's lawless brutality and a lesser-known aspect of the Civil War, the bitter guerrilla conflict in the Appalachian highlands, extending from the Carolinas through Tennessee, Kentuck.